A Study of Coagulation Profile in Sickle Cell Anaemia Patients with and Without Chronic Leg Ulcers at the Ghana Institute of Clinical Genetics, Accra - Sackey, D.S. (University Of Ghana, 2016)
Sickle Cell Anaemia (SCA), the most common form of sickle cell disease (SCD), is associated with elevation of thrombotic factors and depression of anticoagulants, resulting in venous thrombotic events. Sickle Cell Anaemia patients suffer from recurrent, painful, slow-to-heal leg ulcers. Chronic leg ulcer (CLU) in sickle cell anaemia, may not lead to fatal outcomes though, but is associated with aesthetic deformity and reduced quality of life. The pathogenesis of CLU in SCA remains elusive, hampering therapeutic development. Activation of coagulation factors has been shown to be a feature of SCA patients with chronic leg ulcer, with rates of thrombin and fibrin formation constantly higher than normal. Several studies have reported the role of coagulation factors in chronic leg ulcers in SCA, mainly in western countries; there is paucity of data in indigenous Africans with SCA, living in sub-Saharan Africa. Aim: The aim of the study was to determine if there is an association between coagulation profile abnormalities and chronic leg ulcer among SCA patients in Accra. Methods: In this study one hundred and forty-five (145) subjects were assessed to determine their coagulation profile, full blood count and haemoglobin electrophoresis. Fifty (50) SCA with CLU and fifty (50) SCA without Leg Ulcer were recruited from the Ghana Institute of Clinical Genetics, Accra, whilst forty five (45) control subjects with haemoglobin AA were recruited from voluntary blood donors at the National Blood Transfusion Centre, Accra, Ghana. Venous blood sample was collected from each participant for coagulation analysis, Full Blood Count and Hb Electrophoresis. Tests of coagulation analyzed were, prothrombin time (PT), activated partial thromboplastin time (APTT), d-dimer concentration and fibrinogen.
Keywords: Coagulation; Sickle Cell Anaemia; Ulcer; Clinical Genetics